A new memetic approach for the classification rules extraction problem. (1st January 2013) - Benkhider, Sadjia; Drias, Habiba
This paper presents a memetic algorithm applied to the classification rules extraction problem. In our new approach, our aim is to obtain a better results accuracy relatively to that obtained by a standard genetic algorithm (GA). A memetic algorithm is based on a GA which is improved by hybridising a local search approach. We made a hybrid method to compute a model of classification. In the literature, there are many hybridisation forms: in this paper, we have chosen to make our local search algorithm also based on a genetic approach so our hybridisation is purely evolutionary.